2021
DOI: 10.2147/jep.s265282
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Mechanisms and Experimental Pharmacotherapy for L-Dopa-Induced Dyskinesia

Abstract: L-dopa-induced dyskinesia (LID) is the most frequent motor complication associated with chronic L-dopa treatment in Parkinson’s disease (PD). Recent advances in the understanding of the pathophysiological mechanisms underlying LID suggest that abnormalities in multiple neurotransmitter systems, in addition to dopaminergic nigrostriatal denervation and altered dopamine release and reuptake dynamics at the synaptic level, are involved in LID development. Increased knowledge of neurobiological LID substrates has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 158 publications
2
14
0
Order By: Relevance
“…At an advanced stage of PD, a vast portion of dopaminergic neurons are lost, and the serotonergic terminal is mainly providing the DA release and conversion, which are devoid of the molecular mechanism for DA release management and feedback control. As a result, the DA concentration cannot be regulated, which leads to an abnormal swing in extracellular DA concentration following oral administration of L-DOPA ( Mosharov et al, 2015 ; Fabbrini and Guerra, 2021 ). Fluctuations in the dopamine release patterns from the presynaptic neuron terminals give rise to abnormal responses, which were then carried out by postsynaptic neurons.…”
Section: Basic Pathophysiology Of L-dopa-induced Dyskinesiamentioning
confidence: 99%
See 2 more Smart Citations
“…At an advanced stage of PD, a vast portion of dopaminergic neurons are lost, and the serotonergic terminal is mainly providing the DA release and conversion, which are devoid of the molecular mechanism for DA release management and feedback control. As a result, the DA concentration cannot be regulated, which leads to an abnormal swing in extracellular DA concentration following oral administration of L-DOPA ( Mosharov et al, 2015 ; Fabbrini and Guerra, 2021 ). Fluctuations in the dopamine release patterns from the presynaptic neuron terminals give rise to abnormal responses, which were then carried out by postsynaptic neurons.…”
Section: Basic Pathophysiology Of L-dopa-induced Dyskinesiamentioning
confidence: 99%
“…There are two types of glutamatergic receptors: First is ionotropic glutamatergic receptors (iGluRs) that mediate fast excitatory neurotransmission, and the second one is metabotropic glutamatergic receptors (mGluR) that mediate slow excitatory neurotransmission. iGluRs are classified into NMDA, AMPA, and kainite (KA) receptors ( Morin and Di Paolo, 2014 ; Fabbrini and Guerra, 2021 ). Higher striatal expression of NMDA and AMPA receptors was reported previously in MPTP-treated dyskinetic monkeys ( Morin and Di Paolo, 2014 ).…”
Section: Approaches For Management Of Levodopa-induced Dyskinesia: Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…A further novel finding was the negative relationship between the degree of SICF alterations at baseline and the effect of long-term treatment with safinamide on UDysRS-III scores in patients with LID, i.e., the more altered the SICF at S0, the more positive the safinamide-related effect on LID (less worsening or even LID improvement at S2). LID pathophysiology is complex and involves abnormalities in multiple neurotransmitter systems, including dopaminergic, serotoninergic, adrenergic, and glutamatergic, and in the interaction among these systems [5,6,8]. The correlation between SICF alterations at baseline and LID changes at S2 suggests that patients with greater abnormalities in SICF-related glutamatergic circuits are those in whom safinamide produced more beneficial effects on LID.…”
Section: Abnormal Sicf and Lid Pathophysiologymentioning
confidence: 99%
“…A strong relationship between increased glutamatergic activity and the development of L-dopa-induced dyskinesia (LID) is also present in PD [1,5,6]. The role of enhanced glutamatergic transmission in LID has been confirmed by clinical-pharmacological studies, which have shown that antiglutamatergic drugs may improve dyskinesia in patients [7,8].…”
Section: Introductionmentioning
confidence: 97%